PENGARUH LATIHAN FARTLEK TERHADAP DAYA TAHAN KARDIOVASKULER PESERTA EKSTRAKULIKULER KARATE SMK NEGERI 4 PONTIANAK - Sukma, Rachmawati; Hidasari, Fitriana Puspa; Haetami, Mimi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThe problem in this study refers to the implementation of karate extracurricular which is scheduled once a week with an allocation of time for 2 hours is still not enough to increase the endurance status of participants so that the level of endurance of the heart (cardiovascular) of each participant will be different. The purpose of this study was to determine the effect of fartlek training on cardiovascular endurance of karate extracurricular participants in SMK Negeri 4 Pontianak. The method used in this study is an experimental research form Pre-experimental Design, One-Group Pretest-Posttest Design. The subjects in this study were 10 karate extracurricular karate participants in SMK Negeri 4 Pontianak. Data analysis with t-test. Based on the results of the assessment, the value of t_count 6.24> ttable 1.833 shows that it means Ha: accepted and Ho: rejected. If Ha is accepted then the hypothesis reads "the influence of fartlek training on cardiovascular endurance.Â Keywords: Cardiovascular Endurance, Fartlek Exercise